Color Reflectance of Coastal Sediments in the South Bohai Sea and its Implication to Orbital Forcing of East Asian Summer Monsoon - Li, Yibing; Chen, Yanping; Jiang, Xingyu; Yi, Liang (Frontiers in Earth Science, 2021)
There are two distinct variabilities of the East Asian summer monsoon (EASM) on orbital timescales observed in different proxies, and the forcing mechanisms between them are hotly debated. One of the ways to reconcile the debate is to present a geological archive recording two cycles in dominance and somehow in equivalence. In this work, we retrieved an EASM record by studying color reflectance of coastal sediments in the south Bohai Sea, East Asia. The leading component of reflectance derivative spectra accounts for 58.9% variance in total and its loading spectrum can be well correlated to that of mineral assemblages of illite and goethite. For this monsoonal record, orbital variabilities in precession and eccentricity bands are highlighted. By comparing this monsoonal record to previously published proxies, it is speculated that the spectral difference in the sediments of the south Bohai Sea and between various proxies in the EASM domain may indicate an integrated forcing of solar insolation and ice-sheet evolution in the late Quaternary. Overall, the monsoonal record in the Bohai Sea offers an opportunity to fill the gap of the diverse periodicities between various proxies, which is critical to extending our understanding of the EASM on orbital timescales.